Relationship between Mechanical Properties and Microstructure in a New High Strength β Titanium Alloy. Issue 8 (August 2017) - Wei, Zhou; Peng, Ge; Yongqing, Zhao; Shewei, Xin; Qian, Li; Jing, Wang; Chaowen, Huang; Jun, Chen
Abstract: A new high strength titanium alloy containing elements Cr, Fe, Mo, W and Al was designed in order to achieve an excellent combination of ultra-high strength and good fracture toughness. Both the α/β and β heat treatment were introduced to study the effect of microstructure on mechanical properties of the alloy. The result shows that the alloy with α/β solution plus aging treatment is composed of mixture microstructures including a few equiaxed or short billet-like primary α phase and fine lamellar secondary α phase. The alloy has an excellent combination of ultra-high strength and good fracture toughness. The corresponding tensile strength exceeds 1400 MPa and fracture toughnesses K IC is up to 50.7 MPa-m 1/2 . Compared with the alloy after α/β heat treatment, the alloy with β region heat treatment presents representative Widmanstatten structure which has higher fracture toughnesses and lower strengths than the bimodal microstructure.